1999
DOI: 10.1007/s007840050089
|View full text |Cite
|
Sign up to set email alerts
|

Time-related bisphenol-A content and estrogenic activity in saliva samples collected in relation to placement of fissure sealants

Abstract: It was recently reported that estrogenic activity was detected in saliva samples collected during 1 h after placement of one fissure sealant (Delton) and this related to Bisphenol-A (BPA) content. The aim of the present study was to determine the time-related BPA content and estrogenic activity in saliva samples collected before and after placement of two fissure sealants each with a different monomer composition. Eight healthy male volunteers with no history of prior placement of fissure sealants or composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
78
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(92 citation statements)
references
References 13 publications
10
78
0
4
Order By: Relevance
“…BPA was found in the saliva within few minutes after a dental treatment, but at considerably lower levels than previously reported. BPA became undetectable 1 and 24 h after the placement of the sealant [10,12]. It was concluded that due to the low level of BPA, there was no clinical risk after placement of fissure sealants, an assumption that was confirmed by other authors [10,13,14].…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…BPA was found in the saliva within few minutes after a dental treatment, but at considerably lower levels than previously reported. BPA became undetectable 1 and 24 h after the placement of the sealant [10,12]. It was concluded that due to the low level of BPA, there was no clinical risk after placement of fissure sealants, an assumption that was confirmed by other authors [10,13,14].…”
mentioning
confidence: 64%
“…Again, these data depend upon the sensitivity of the analytical method. However, it could be clarified that Bis-DMA containing resins rather than Bis-GMA-based resins released BPA shortly after placement and that collected saliva showed estrogenic activity in vitro [10][11][12]. Under hydrolytic conditions, the release of BPA from a fissure sealant into the saliva occurs immediately after the placement of the sealant.…”
mentioning
confidence: 99%
“…[1][2][3] With a worldwide annual production estimated to be more than 3.5 million tons, BPA has shown endocrine-disrupting effects and potential adverse health effects. 4,5 These may cause severe environmental health problems and have thus triggered the increasing public concerns.…”
Section: Introductionmentioning
confidence: 99%
“…I am concerned about continued reference to this study. Ashby (2) (3)(4)(5). On the other hand, BPDMA is a component of the sealant used in their study.…”
mentioning
confidence: 99%
“…On the other hand, BPDMA is a component of the sealant used in their study. Therefore, leaching of a small amount of unpolymerized BPDMA is likely (3,4). Furthermore, the detection of BPA derived from BPDMA in saliva is likely because BPDMA is easily hydrolyzed to BPA in saliva (6) Olea's Response…”
mentioning
confidence: 99%